Saneamento básico: arranjos institucionais e contratuais para a universalização do serviço no Brasil - Amaral, Edinaldo Paulo Tenório Veríssimo do (2024)
This dissertation examines, from a legal perspective, the provisions and arrangements under Law nº 14.026/2020, the New Sanitation Framework, which enable the systematization of models aimed at universalizing basic sanitation in Brazil. The research emphasizes sanitation as a fundamental right, associating it with the rights to health and a balanced environment, essential to human dignity and sustainable development. Thus, it highlights the role of the New Framework in establishing ambitious targets for the universalization of services, underscoring the challenges and opportunities brought forth by this legislation. The study analyzes national experiences with public consortia, program contracts, concessions, public-private partnerships, and privatization efforts that have led to significant improvements in coverage and efficiency of sanitation services. Each arrangement is explored in terms of its contribution to regionalized provision and the economic viability of sanitation services, emphasizing the importance of public-private collaboration to enable efficient service delivery across diverse regions with unique needs and characteristics. Furthermore, the study examines various financing structures for sanitation projects, such as incentivized debentures, investment funds, and partnerships with development banks, which are essential for meeting the universalization targets by 2033. Ultimately, the dissertation seeks to provide a consolidated view of the main legal and financial frameworks that enable the sustainable and regionalized provision of sanitation services in Brazil, thus promoting sanitation as a vital component of public health and environmental sustainability